Patient Centricity in Patient Preference Studies: The Patient Perspective - van Overbeeke, Eline; Vanbinst, Inès; Jimenez-Moreno, Aura Cecilia; Huys, Isabelle (Frontiers in Medicine, 2020)
Objectives: A factor contributing to the value of patient preference studies is patient centricity. This study aimed to explore how patients want to be involved in the design and conduct of patient preference studies. In addition, we investigated patients’ expectations regarding the communication of study results back to patients. Methods: Semi-structured interviews were conducted with patient representatives within three different disease areas: rheumatic diseases, cancer and neuromuscular disorders. For each disease area, interviews were conducted with interviewees from Belgium, the Netherlands and the United Kingdom. Interviews followed a predefined interview guide covering topics relating to timing, level, and requirements for patient involvement in patient preference studies, as well as communication of results. Interviews were audio-recorded, transcribed and analyzed using framework analysis in NVivo 12. Results: A total of 14 interviews were conducted. Some interviewees believed that patients should be involved in all steps of a patient preference study. Patient involvement seemed most valuable during the design phase to support defining research questions and instrument design. During analysis, patients can be involved for optimal interpretation of results. Most interviewees mentioned that patient involvement should be on the level of advice or collaboration, not control. Interviewees expressed requirements for patient involvement relating to the knowledge of the involved patient, time investment, compensation and other incentives. Regarding communication of results, most interviewees wished to receive a brief and lay summary of the results, followed by a detailed explanation of both individual and average results accompanied by visuals. Conclusions: Patient involvement in patient preference studies could increase question understanding of study participants and ensure correct interpretation of results by researchers. Patients want to be involved as advisors or collaborators, and considering their personal situation as well as establishing agreements on roles, time involvement and compensation early on will result in a most optimal partnership.